Principles of the JCEL Publication Agreement: Stakeholders, Copyright, and Policy Positions - Crews, Kenneth D. (Journal of Copyright in Education & Librarianship, 2016)
Every academic, scholarly, or professional journal should have a publication agreement for contributing authors to sign – but only if the agreement is good.  A well-considered agreement is a chance to create an improved relationship among authors, publishers, and readers.  By contrast, a bad agreement can do real damage.  The Editorial Board of the Journal of Copyright for Education and Librarianship (“JCEL”) deliberated thoroughly the details of the agreement it offers to contributing authors, with the quest of putting into practice our principles about the relationship of copyright and scholarly works, in service to our community of stakeholders.This article is intended to capture and document the Board’s reflections on the JCEL agreement with two leading objectives: To explain to contributing authors the meaning and significance of various provisions in the agreement, and to serve as a motivation and resource for editors of other journals as they engage in a fresh examination of their agreements.  This article offers a bit of explanatory background and a hint of some of the internal give and take that led to the final version.  Although our publication agreement should be regularly reexamined, with future changes to meet changing needs, the principles underlying the current draft should remain steady.